The Japanese Production System and Its International Transferability (Malaysian Management Journal, 1997)
The Japanese production system has an ethnic or national basis. There are considered to be three production components of the system-shop-floor-centred work organization, waste-free production control, and participative management in the context of cooperative labour relations. For each of these, it is possible to set up a Japanese-type'. The author is conducting research into the overseas operations of Japanese subsidiaries in automobile assembly. Japanese multinational enterprises presumably try to apply the system to their overseas operations to take advantage of its strengths; however, given that they have moved into a foreign country, presumably Japanese enterprises have to adapt to the management environment of the local area. This research investigates the following questions: (i) Does this 'application' and 'adaptation' result in a dilemma? (ii) What is actually being applied and what has not been possible to apply? (iii) How well is the balance between 'application' and 'adaptation' being achieved? According to surveys of Japanese manufacturing plants in North America, Asia, and Europe, the application of the system is possible. Of course this does not mean that it can be applied 100%. The pattern of application varies according to the management strategy of the Japanese enterprises.